Clinical Prevalence of osteoporosis in Nepalese COPD patients - Kumar, Sankalp; Paudel, Sushil; Lakhey, Rajesh Bahadur; Adhikari, Sirish; Pokharel, Rohit Kumar (Nepal Orthopaedic Association Journal, 2023)
INTRODUCTION: Osteoporosis is a systemic skeletal disease characterized by low bone mass and micro-architectural weakening of the bone. Osteoporosis is often undiagnosed, overlooked, and undertreated by patients and physicians. Osteoporosis is common in people with COPD. Present study aims to investigate the prevalence of osteoporosis in individuals with COPD. METHODS: Total of 80 COPD patients admitted in Respiratory ward of Tribhuvan University Teaching Hospital, Kathmandu were included in this study. Demographic information of the patients, their BMI, smoking habit, use of steroid and diabetes as co-morbidity were recorded. They were categorized using Global initiative for chronic Obstructive Lung Disease (GOLD) criteria. All patients underwent for bone mineral densitometry (BMD) using quantitative ultrasound (QUS) from distal radius and anterior tibial crest. Status of the BMD in COPD patients with different severity according to the GOLD criteria, association of osteoporosis with other parameters was analyzed. Prevalence of vertebral fracture among the COPD patients was also noted. RESULT: The mean age of the patients was 68.58± (9.389) years, and the male to female ratio was M: F = 1: 1.35. Out of 80 patients 68 (85%) were smoker, 24 (30%) were diabetic and 67 (83.8%) were taking glucocorticoids. Overall BMD was low in 82.5% (osteopenia in 56.25% and osteoporosis in 26.25%) of COPD patients. Osteoporosis was observed in 12.5 %, 30.2% 38.4% of patients with GOLD II, III and IV COPD respectively. Mean BMI of patients were 26.014± (3.600), 23.198± (3.020) and 21.428± (3.084) respectively in normal BMD, osteopenia and osteoporosis (P =0.000) groups. Number of smokers was significantly more in low BMD patients (P = 0.000). Diabetes mellitus was a co-morbid condition in 24 patients (30%); but it was not correlated with level of BMD (P = 0.927). Use of oral or inhale glucocorticoids was also not correlated with level of BMD (P=0.591). There were 5(10.8%) patients who had single level vertebral insufficiency fractures. CONCLUSION: There is higher prevalence of osteoporosis in patients with COPD and it is directly correlated with severity of the COPD, smoking and BMI. Vertebral fracture may be one of the comorbidity in COPD.